Subclone-specific microenvironmental impact and drug response in refractory multiple myeloma revealed by single‐cell transcriptomics - Tirier, Stephan Marius; Mallm, Jan-Philipp; Steiger, Simon; Poos, Alexandra; Awwad, Mohamed; Giesen, Nicola; Casiraghi, Nicola; Susak, Hana; Bauer, Katharina; Baumann, Anja; John, Lukas; Seckinger, Anja; et al. (Nature Communications, 2021)
Relapsed/refractory multiple myeloma (RRMM) is characterized by a remarkable heterogeneity and high drug resistance. Here, the authors analyse RRMM samples by single-cell RNA-sequencing, revealing molecular features associated with high-risk chromosomal 1q-gain and changes in the tumor microenvironment.
Gesehen am 03.12.2021